Revisiting the Feldstein-Horioka Puzzle: An Institutional Sector View - Bebczuk, Ricardo Néstor (2007)
Working on a unbalanced sample of OECD countries spanning the period 1970-2003, this paper contributes to the empirical literature on the Feldstein-Horioka puzzle by making three main innovations: First, it goes beyond the traditional national-level investment-saving equations to estimate, for the first time, regressions at the institutional sector level (households, corporations, and government). Second, it explores the implications of giving separate consideration to current account deficits and surpluses. Lastly, it uses advanced panel data techniques to deal with endogeneity and to distinguish long- and short-run effects. New and provocative results emerge from the analysis.